2014
DOI: 10.1002/2014gl061895
|View full text |Cite
|
Sign up to set email alerts
|

Has the number of Indian summer monsoon depressions decreased over the last 30 years?

Abstract: Monsoon depressions are cyclonic atmospheric vortices with outer radii near 1000 km that form within the larger‐scale monsoon circulations of India and other regions. Recent studies have reported a downward trend in recent decades in the number of Indian summer monsoon depressions. In particular, the years 2002, 2010, and 2012 were noted for having the first summers, in over a century, in which no depressions formed. Here satellite and reanalysis data are used to document the existence of multiple storms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Some recent studies have reported that there are differences in the trend in the number of MDs extracted from the reanalysis data sets and traditional India Meteorological Department (IMD) data set (Cohen and Boos, 2014;. At the same time, Praveen et al (2015) have shown that the number of low-pressure systems extracted from the reanalysis data, using conventional detection algorithm based on the closed isobars in the surface pressure field, is well matched with traditional IMD data set.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some recent studies have reported that there are differences in the trend in the number of MDs extracted from the reanalysis data sets and traditional India Meteorological Department (IMD) data set (Cohen and Boos, 2014;. At the same time, Praveen et al (2015) have shown that the number of low-pressure systems extracted from the reanalysis data, using conventional detection algorithm based on the closed isobars in the surface pressure field, is well matched with traditional IMD data set.…”
Section: Introductionmentioning
confidence: 91%
“…Some recent studies have reported that there are differences in the trend in the number of MDs extracted from the reanalysis data sets and traditional India Meteorological Department (IMD) data set (Cohen and Boos, ; Hunt et al ., ). At the same time, Praveen et al .…”
Section: Introductionmentioning
confidence: 98%
“…For instance, the July 2010 flooding in Pakistan (Galarneau et al, 2012) and June 2013 flooding in Uttarakhand, India (Singh et al, 2014), were the result of prolonged periods of intense rainfall during the lifecycle of MDs, with a combined total of over $10 billion in economic losses and over 5,000 deaths (Sharjeel et al, 2012). However, a recent study questioned the accuracy of the Indian Meteorological Department MD archives and the associated decreasing trends (Cohen & Boos, 2014). Several observational studies, based on the records of the Indian Meteorological Department archives, indicate a decreasing trend in MDs over the last 40 years, related to the anomalies in the monsoon dynamics (e.g., weakening of the upper troposphere tropical easterly jet; Dash et al, 2004;Rao et al, 2004) and/or in the thermodynamics (e.g., a decrease in midtroposphere relative humidity; Prajeesh et al, 2013;Vishnu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This observed frequency shift is poorly understood, even though several mechanisms related to climate change and aerosol have been proposed [e.g., Dash et al ., ; Jadhav and Munot , ; Prajeesh et al ., ; Krishnamurti et al ., ]. However, recently, Cohen and Boos [] posed the question whether there has been a decreasing trend in the depressions, since they could not detect a trend in the frequency of depressions in the distinctive LPS data sets constructed using different automated detection methods.…”
Section: Introductionmentioning
confidence: 99%